2017
DOI: 10.1177/0892705717697780
|View full text |Cite
|
Sign up to set email alerts
|

Transient thermal analysis of laser-assisted thermoplastic tape placement at high process speeds by use of analytical solutions

Abstract: This article presents a transient thermal analysis of laser-assisted thermoplastic tape placement at high process speeds. The article revises modeling simplifications made in the literature and introduces novel ones. Analytical solutions to the thermal problem are proposed, for the heating and the cooling period. The process analysis of high speeds assumes a high-power laser in combination with a well-functioning temperature control. Due to this assumption, the final (surface) temperature is kept equal in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Kim et al 64 used a 2-D steady-state model, however, suggested that a detailed analysis considering a 3-D model is necessary due to the nonuniform hot gas impingement condition. Weiler et al 71 presented a 1-D transient model of a laser-assisted winding process and considered heat accumulation (heat reaching the back of tape or substrate) as a key phenomenon for the process, suggesting this effect needs further analysis and investigation. More 1-D transient models were reported 36,37,43,71,82,110,143 as well as 1-D steady-state gas impingement models.…”
Section: Process Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Kim et al 64 used a 2-D steady-state model, however, suggested that a detailed analysis considering a 3-D model is necessary due to the nonuniform hot gas impingement condition. Weiler et al 71 presented a 1-D transient model of a laser-assisted winding process and considered heat accumulation (heat reaching the back of tape or substrate) as a key phenomenon for the process, suggesting this effect needs further analysis and investigation. More 1-D transient models were reported 36,37,43,71,82,110,143 as well as 1-D steady-state gas impingement models.…”
Section: Process Modelingmentioning
confidence: 99%
“…Weiler et al 71 presented a 1-D transient model of a laser-assisted winding process and considered heat accumulation (heat reaching the back of tape or substrate) as a key phenomenon for the process, suggesting this effect needs further analysis and investigation. More 1-D transient models were reported 36,37,43,71,82,110,143 as well as 1-D steady-state gas impingement models. 30,31,138,148 It is obvious that most of the simulation works are based on 2-D and 1-D models with major assumptions being adopted.…”
Section: Process Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured temperature was compared with the opticalthermal model predictions. An analytical thermal model was developed in [40] for a LATP process. It was found that the through-thickness temperature was significantly affected by the high process speed.…”
Section: Introductionmentioning
confidence: 99%